PAMETNA SPECIJALIZACIJA I KONKURENTNOST U OKVIRU INDUSTRIJE 5.0 - Sterev, Nikolay; Milusheva , Vyara (International Journal of Economic Practice and Policy, 2025)
As the business world survived after the COVID -19 pandemics, according to “traditional” Porters’ competitiveness models, the traditional industrial sectors lose their competitive advantage. So, they have to do “some” virtualization in order to be more competitive at common economic world. The paper aims to discuss possibilities of smart specialization for increasing competitiveness of traditional industrial sectors. The bases for analysis is the needed of traditional industries for smart change under the Industry 5.0 in order survive at digital business world. But, how such digital and smart specialization to be done is the key problem discussed at the paper. The main results of the desk and practical research in the paper are found in the next points: 1. Application of Industry 5.0’ competitive approach to the “old” traditional industries and 2. Introduction of competitive roadmap based on smart specialization and social platforms.